2019
DOI: 10.1097/fbp.0000000000000505
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial metabolism: a common link between neuroinflammation and neurodegeneration

Abstract: Neurodegenerative disorders have been considered as a growing health concern for decades. Increasing risk of neurodegenerative disorders creates a socioeconomic burden to both patients and care givers. Mitochondria are organelle that are involved in both neuroinflammation and neurodegeneration. There are few reports on the effect of mitochondrial metabolism on the progress of neurodegeneration and neuroinflammation. Therefore, the present review summarizes the potential contribution of mitochondrial metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 93 publications
2
32
0
Order By: Relevance
“…M, module; C, confidence. also reported that the mitochondrial citric acid cycle can regulate the pathogenesis of neuroinflammation and neurodegeneration (Garabadu et al, 2019). The identified genes that play a role in one or more of these pathways included COX6C, UQCRB, and NDUFA5.…”
Section: Discussionmentioning
confidence: 94%
“…M, module; C, confidence. also reported that the mitochondrial citric acid cycle can regulate the pathogenesis of neuroinflammation and neurodegeneration (Garabadu et al, 2019). The identified genes that play a role in one or more of these pathways included COX6C, UQCRB, and NDUFA5.…”
Section: Discussionmentioning
confidence: 94%
“…Inflammatory markers, including C-reactive protein [ 120 ] and IL-6 [ 75 ] and oxidative stress markers nitric oxide and hydroxyl radical have been found to be elevated in the CSF of patients with PD-MCI and correlate with lower MoCA scores [ 75 ]. Mitochondrial dysfunction can lead to an increase in oxidative stress as well as glial and astrocyte dysfunction, contributing to an abnormal inflammatory response [ 121 , 122 , 123 ]. In PDD, deficiency in mitochondrial complex 1 activity and reduced mitochondrial DNA levels in the prefrontal cortex, compared to healthy controls, have been described [ 124 ].…”
Section: Risk Factors For Cognitive Decline In Parkinson Diseasementioning
confidence: 99%
“…Mitochondria are intracellular organelles that regulate energy metabolism, the production of reactive oxygen species (ROS), cellular signaling, Ca 2+ homeostasis, and apoptosis. Studies revealed that the mitochondrial dysfunction and damage play a crucial role in the development of neurodegenerative diseases, including amyotrophic lateral sclerosis, Alzheimer's disease, Parkinson's disease, Huntington's disease or multiple sclerosis, by enhancing innate and adaptive immune responses that result in neuroinflammation [55]. The dysfunction of mitochondria and impaired energy metabolism were also reported in the pathophysiology of mood disorders such as bipolar disorder and major depressive disorder [56][57][58][59].…”
Section: Energy Metabolism Markers Of Microglia Activationmentioning
confidence: 99%